Melatonin Is a Potential Target for Improving Post-Harvest Preservation of Fruits and Vegetables - Xu, Tao; Chen, Yao; Kang, Hunseung (Frontiers in Plant Science, 2019)
Melatonin is a ubiquitous molecule distributed in nature and not only plays an important role in animals and humans but also has extensive functions in plants, such as delaying senescence, exerting antioxidant effects, regulating growth and development, and facilitating plant adaption to stress conditions. Endogenous melatonin is widespread in fruits and vegetables and plays important roles in the ripening and post-harvest process of fruits and vegetables. Exogenous application of melatonin removes excess reactive oxygen species from post-harvest fruits and vegetables by increasing antioxidant enzymes, non-enzymatic antioxidants, and enzymes related to oxidized protein repair. Moreover, exogenous application of melatonin can increase endogenous melatonin to augment its effects on various physiological processes. Many previous reports have demonstrated that application of exogenous melatonin improves the post-harvest preservation of fruits and vegetables. Although overproduction of melatonin in plants via transgenic approaches could be a potential means for improving the post-harvest preservation of fruits and vegetables, efforts to increase endogenous melatonin in plants are limited. In this review, we summarize the recent progress revealing the role and action mechanisms of melatonin in post-harvest fruits and vegetables and provide future directions for the utilization of melatonin to improve the post-harvest preservation of fruits and vegetables.